2019
DOI: 10.1371/journal.pone.0221023
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant resting-state functional connectivity of the dorsolateral prefrontal cortex to the anterior insula and its association with fear avoidance belief in chronic neck pain patients

Abstract: Chronic neck pain (CNP), a global health problem, involves a large amount of psychological and socioeconomic burdens. Not only physical causes but also behavioral disorders such as a fear-avoidance belief (FAB) can associate with the chronicity of neck pain. However, functional brain mechanisms underlying CNP and its related behavioral disorders remain unknown. The aim of the current resting-state functional magnetic resonance imaging (fMRI) study was to explore how the functional brain networks differed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Guided by previous findings regarding brain alterations in patients with chronic neck pain, ROI-to-ROI ( Whitfield-Gabrieli and Nieto-Castanon, 2012 ) rsFC analyses were conducted with the following seed regions: precuneus, posterior cingulate cortex, left and right insula, left and right amygdala, anterior cingulate cortex, medial prefrontal cortex, left and right hippocampus, left and right thalamus, left and right pallidum, left and right temporal pole, left and right superior parietal cortex, left and right precentral gyrus, left and right superior temporal gyrus anterior and posterior division, left and right supramarginal gyrus anterior and posterior division, left and right frontal operculum, left and right middle frontal gyrus, left and right frontal orbital cortex, left and right postcentral gyrus, left and right superior frontal gyrus, and left and right frontal pole. These seeds (i.e., 22 seeds bilateral; 40 seeds when taking left and right separate) are observed to be structurally or functionally altered in previous studies in the chronic neck pain population of the present study ( Coppieters et al, 2017b , Coppieters et al, 2018 , De Pauw et al, 2019a , De Pauw et al, 2019b ) or in another chronic neck pain sample ( Ihara et al, 2019 ) compared to healthy controls. Also, seeds were selected based on our previously observed significant associations between structural or functional brain characteristics and pain-related measures in CINP and CWAD.…”
Section: Methodssupporting
confidence: 49%
See 3 more Smart Citations
“…Guided by previous findings regarding brain alterations in patients with chronic neck pain, ROI-to-ROI ( Whitfield-Gabrieli and Nieto-Castanon, 2012 ) rsFC analyses were conducted with the following seed regions: precuneus, posterior cingulate cortex, left and right insula, left and right amygdala, anterior cingulate cortex, medial prefrontal cortex, left and right hippocampus, left and right thalamus, left and right pallidum, left and right temporal pole, left and right superior parietal cortex, left and right precentral gyrus, left and right superior temporal gyrus anterior and posterior division, left and right supramarginal gyrus anterior and posterior division, left and right frontal operculum, left and right middle frontal gyrus, left and right frontal orbital cortex, left and right postcentral gyrus, left and right superior frontal gyrus, and left and right frontal pole. These seeds (i.e., 22 seeds bilateral; 40 seeds when taking left and right separate) are observed to be structurally or functionally altered in previous studies in the chronic neck pain population of the present study ( Coppieters et al, 2017b , Coppieters et al, 2018 , De Pauw et al, 2019a , De Pauw et al, 2019b ) or in another chronic neck pain sample ( Ihara et al, 2019 ) compared to healthy controls. Also, seeds were selected based on our previously observed significant associations between structural or functional brain characteristics and pain-related measures in CINP and CWAD.…”
Section: Methodssupporting
confidence: 49%
“…These finding are in line with previous studies. For instance, Ihara et al recently also revealed aberrant prefrontal rsFC in patients with chronic neck pain compared to healthy controls, albeit in coupling of the dorsolateral prefrontal cortex ( Ihara et al, 2019 ). Also in our previous graph analytical resting-state analysis, we found alterations in the amygdala ( De Pauw et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, significant alterations in the brain structure and function of NP patients have been reported by neuroimaging studies. Compared to healthy subjects, NP patients shown decreased functional activity in the left sensorimotor cortex and right temporoparietal junction [ 20 ], as well as increased functional connectivity between the right dorsolateral prefrontal cortex and the right anterior insula, which are associated with pain intensity [ 21 ]. Based on these findings, neuroimaging techniques appear to be useful tools for investigating the central mechanisms of acupuncture therapy for NP.…”
Section: Introductionmentioning
confidence: 99%